2014
DOI: 10.11138/ccmbm/2014.11.3.181
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for the diagnosis of sarcopenia

Abstract: SummarySarcopenia is an age-related process of skeletal muscle loss associated with declining physical performance, highly prevalent among older subjects, with a negative prognostic effect on falls, disability and mortality risk. Modern approaches to sarcopenia case finding and diagnosis are based on physical performance measures, while assessment of muscle mass represents the second diagnostic step. Muscle mass can be quantified at different levels of body composition, with a complexity increasing from atomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 30 publications
1
85
0
10
Order By: Relevance
“…Although previous epidemiologic studies 20, 21 in hemodialysis patients have reported that higher muscle mass, representing by higher quartile of mid-arm muscle circumference, was significantly associated with greater survival, those studies analyzed the data by using arbitrary cutpoints for high muscle mass derived from within their cohort rather than cutpoints derived from normative data from young, healthy individuals as recommended in the definition of sarcopenia. 2, 3, 11 In addition, reliance on anthropometric measures in those studies could lead to misclassification because of interobserver variation 22 and fatty infiltration of muscle compartments that occurs with atrophy. 23 Isoyama and colleagues 10 also recently found that patients new to dialysis with low muscle mass (defined as appendicular muscle mass by DXA/height 2 at least 2 SDs below the sex-specific mean of young adults) were not at higher risk of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous epidemiologic studies 20, 21 in hemodialysis patients have reported that higher muscle mass, representing by higher quartile of mid-arm muscle circumference, was significantly associated with greater survival, those studies analyzed the data by using arbitrary cutpoints for high muscle mass derived from within their cohort rather than cutpoints derived from normative data from young, healthy individuals as recommended in the definition of sarcopenia. 2, 3, 11 In addition, reliance on anthropometric measures in those studies could lead to misclassification because of interobserver variation 22 and fatty infiltration of muscle compartments that occurs with atrophy. 23 Isoyama and colleagues 10 also recently found that patients new to dialysis with low muscle mass (defined as appendicular muscle mass by DXA/height 2 at least 2 SDs below the sex-specific mean of young adults) were not at higher risk of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…An assessment of whole‐body composition by DXA has been increasingly used both in clinical and research practice because it provides an optimal combination of accuracy, cost, and safety. It is acknowledged by many practitioners as the most accurate method for estimating body composition in clinical practice …”
Section: Introductionmentioning
confidence: 99%
“…The more recent methods like bioelectrical impedance analysis (BIA), dual energy x‐ray absorptiometry (DEXA) and air displacement plethismography are recognized as the indirect methods of assessing body composition in particular the muscle mass . In recent times, computed tomography (CT) has emerged as a more sensitive and specific measure of assessing both adiposity and muscle mass . Hence, this study was planned to characterize the body composition in patients with alcoholic cirrhosis using a precise gold standard method of computed tomography and also to define sarcopenia based on the carefully derived cut‐offs from healthy controls.…”
Section: Introductionmentioning
confidence: 99%